Svjedočenje o humanosti u kriznome dobu / Testimony of Humanity in the Age of Crisis - Duraković, Esad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
This text is a presentation of the book Faith through love is Effective. Book of Proceedings on the Occasion of the 70th Birthday of Franjo Topić, Human Brotherhood Foundation, Synopsis, Novi Travnik-Sarajevo-Zagreb, 2024.